Atomic-resolution imaging of rutile TiO2(110)-(1 × 2) reconstructed surface by non-contact atomic force microscopy - Katsube, Daiki; Ojima, Shoki; Inami, Eiichi; Abe, Masayuki (Beilstein Journal of Nanotechnology, 2020)
The structure of the rutile TiO2(110)-(1 × 2) reconstructed surface is a phase induced by oxygen reduction. There is ongoing debate about the (1 × 2) reconstruction, because it cannot be clarified whether the (1 × 2) structure is formed over a wide area or only locally using macroscopic analysis methods such as diffraction. We used non-contact atomic force microscopy, scanning tunneling microscopy, and low-energy electron diffraction at room temperature to characterize the surface. Ti2O3 rows appeared as bright spots in both NC-AFM and STM images observed in the same area. High-resolution NC-AFM images revealed that the rutile TiO2(110)-(1 × 2) reconstructed surface is composed of two domains with different types of asymmetric rows.
Keywords: non-contact atomic force microscopy; (1 × 2) reconstruction; rutile; surface structure; titanium dioxide (TiO2)